Football Players' Satisfaction: An exploratory factor analysis / Azlina Zid ...[et al.] - Zid, Azlina; Amiruddin, Rozita; Rajli, Mohammad Adzly; Ismail, Siti Sakinah (Faculty of Sports Science and Recreation, 2017)
This study aims at identifyin the constructs in the Athlete Satisfaction Questionnaire from the perspective of the football players. To date, empirical study on athletes' satisfaction construct especially in the football sport has been limited. 250 professional football players from the Malaysian Super and Premiere League were involved in this study. Athlete Satisfaction Questionnaire developed by Reimer and Chelladurai (1997) was used and the exploratory factor analysis was done to obtain information pertaining to this current study. The study findings showed that from the 14 constructs that existed in the Athlete Satisfaction Questionnaire, only 5 constructs had been formed. The outcome showed that the training and instruction, also personal treatment were included in the same factor. This is not surprising as the items had given the same picture through the support and motivation of the coaches towards the players. The five constructs had given a greater eigenvalue than 1. Through the Rotated Sums of Squared Loadings analysis, the five constructs predicted as much as 77.47% overall change of variance for the variable 'athletes satisfaction'(Factor 1 = 20.65%; Factor 2 = 19.18%; Factor 3 = 13.07%; Factor 4 = 12.99%; Factor 5 = 11.58%)